Carbon dots for photothermal applications - Balou, Salar; Shandilya, Pooja; Priye, Aashish (Frontiers in Chemistry, 2022)
Carbon dots are zero-dimensional nanomaterials that have garnered significant research interest due to their distinct optical properties, biocompatibility, low fabrication cost, and eco-friendliness. Recently, their light-to-heat conversion ability has led to several novel photothermal applications. In this minireview, we categorize and describe the photothermal application of carbon dots along with methods incorporated to enhance their photothermal efficiency. We also discuss the possible mechanisms by which the photothermal effect is realized in these carbon-based nanoparticles. Taken together, we hope to provide a comprehensive landscape highlighting several promising research directions for using carbon dots for photothermal applications.